Surgical repair of a tibial fracture in a Belgian Landrace pig - Vertenten, G.; Martens, A.; Declercq, J.; Schauvliege, S.; Weiland, L.; Gasthuys, F. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
This paper reports the surgical treatment of a tibial fracture in a castrated adult male Belgian Landrace pig of 180 kg. The fracture was repaired using an intramedullary Steinmann pin, combined with cerclage wire and external transfixation. In contrast to other animal species, the fracture repair in the pig was hindered by the short and curved bones, the thick subcutaneous fat layer and the pronounced musculature. Postoperatively, the pig developed an osteomyelitis of the tibia due to pin tract contamination. Despite this complication, the fracture healed acceptably when all fixation material was removed two months after surgery. The infection resolved quickly and a satisfactory clinical result was obtained.
Keywords: Tibia; fracture; surgical treatment; osteomyelitis; pig